How to develop a structural conception of algebra of school students - Hatisaru, Vesife (LUMAT-B: International Journal on Math, Science and Technology Education, 2022)
Algebra plays a pivotal role in school students’ mathematics learning. Students, however, have serious difficulties especially with ‘seeing’ the algebraic structures and expressing generality with algebraic symbols. These skills are not gained accidently; developing them in students takes continuous, sustained, and focused effort from both students themselves and teachers. As teachers of mathematics, what kind of classroom experience could we provide our students to prepare them for using algebra successfully? How could we assist them to develop structural conceptions of algebra? In this paper, I describe an approach based on the Mathematical Habits of Mind framework (Cuoco et al., 1996) as a response to these questions and provide examples of how this approach may look in the classroom.